Teaching the economics of terrorism and war - Jahangir, Junaid (My University, 2026)
The objective in this paper is to delineate the salient ideas in the economics of terrorism and the economics of war. A review of the academic literature and popular books allows to list key ideas from diverse areas including the economics of terrorism, political economy of war, economics of war, conflict economics, and economics of arms. These ideas allow for a lesson plan around sample questions and suggested answers that are complemented with resources based on popular books, media articles, and video clips. Thus, instead of embroiling students with stylized mathematical problems or indifference curve analysis, the idea is to allow both instructors and students in economics to grapple with salient ideas in the economics of terrorism and the economics of war.
Keywords: economics of terrorism; economics of war; political economy of war; conflict economics; economics of arms